Acinetobacter baumannii utilizes a novel protective factor to combat desiccation-induced oxidative stress - John M. Farrow; Greg Wells; Everett C. Pesci (PLoS ONE, 2026)
One of the factors that facilitates the nosocomial spread of the frequently multidrug-resistant pathogen Acinetobacter baumannii is its ability to persist on dry surfaces for weeks. These bacteria do not form spores, but instead rely on a group of protective factors to survive desiccation. We investigated a protective factor of unknown function, referred to here as desiccation tolerance protein C (DtpC), which we found to be co-transcribed with another protective factor, the KatE catalase. A Δ dtpC Δ katE mutant strain had a greatly decreased ability to survive desiccation, but complementation with either dtpC or katE individually could restore survival to the wild-type level, showing that DtpC and KatE are each sufficient for desiccation tolerance. Since KatE also protects cells from oxidative stress, we examined whether oxygen had an effect on desiccation survival, and analyzed the formation of reactive oxygen species in dried cells. Compared to the wild-type strain, the Δ dtpC Δ katE mutant strain was much more sensitive to the detrimental effects of oxygen during desiccation, and we observed that hydrogen peroxide accumulated in dried cells of the Δ dtpC Δ katE mutant strain over time, whereas hydrogen peroxide levels were limited when either dtpC or katE was present. Additionally, either dtpC or katE was sufficient to limit desiccation-induced mutagenesis, which is driven by DNA damage during drying. By using structural predictions and site-directed mutagenesis, we found that DtpC’s protective activity depends on a domain that is similar to heme-oxygenase-like diiron oxidases. No other proteins in this family have been linked to desiccation tolerance or oxidative stress, making DtpC a novel type of protective factor. Overall, our data show that both DtpC and KatE act to limit desiccation-induced oxidative stress, which is critical for A. baumannii to survive on dry surfaces.